2021
DOI: 10.1016/j.jcmgh.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Enterohepatic Transcription Factor CREB3L3 Protects Atherosclerosis via SREBP Competitive Inhibition

Abstract: Background & Aims cAMP responsive element-binding protein 3 like 3 (CREB3L3) is a membrane-bound transcription factor involved in the maintenance of lipid metabolism in the liver and small intestine. CREB3L3 controls hepatic triglyceride and glucose metabolism by activating plasma fibroblast growth factor 21 (FGF21) and lipoprotein lipase. In this study, we intended to clarify its effect on atherosclerosis. Methods CREB3L3-deficifient, liver-specific CREB3L3 knockout, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…The results of this study fit well with previous work showing that hepatic and intestinal CREB3L3 contribute to cholesterol metabolism. 10,11,13 Consistent with a previous report that CREB3L3 controls liver X receptor signaling, 17 Nakagawa et al 15 also confirmed decreased liver X receptor signaling and an increased lipid content in the intestines of LDLR -/-CREB3L3 -/mice. However, in contrast to previously published findings showing that the atherogenic phenotype of CREB3L3 mice is dependent on plasma FGF21, 5,11,18 in the current study the deficiency of FGF21 in LDLR -/-Tg CREB3L3 mice did not negate the amelioration of arteriosclerosis, suggesting that FGF21 is not the sole contributor to the anti-arteriosclerosis effects of CREB3L3.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study fit well with previous work showing that hepatic and intestinal CREB3L3 contribute to cholesterol metabolism. 10,11,13 Consistent with a previous report that CREB3L3 controls liver X receptor signaling, 17 Nakagawa et al 15 also confirmed decreased liver X receptor signaling and an increased lipid content in the intestines of LDLR -/-CREB3L3 -/mice. However, in contrast to previously published findings showing that the atherogenic phenotype of CREB3L3 mice is dependent on plasma FGF21, 5,11,18 in the current study the deficiency of FGF21 in LDLR -/-Tg CREB3L3 mice did not negate the amelioration of arteriosclerosis, suggesting that FGF21 is not the sole contributor to the anti-arteriosclerosis effects of CREB3L3.…”
supporting
confidence: 83%
“…In summary, Nakagawa et al 15 have enhanced our understanding of the complex regulation of lipid metabolism, showing a functional competition between CREB3L3 and SREBP and its consequences to the progress of arteriosclerosis. Therapeutic strategies designed to modulate CREB3L3 and/or SREBP cleavage, trafficking, or subcellular localization might be beneficial in the treatment of hyperlipidemia, arteriosclerosis, and obesity-associated metabolic diseases.…”
mentioning
confidence: 99%
“…CREBH overexpression in LDLR KO mice increases apolipoprotein-related genes, such as Apoa1, Apoa4, Apoa5, and Apoc2, which stimulates LPL-mediated triglyceride clearance (Figures 2 and 3) [40,52]. Conversely, deficiency of CREBH in LDLR KO mice reduces the expression of these genes, thereby inducing hypertriglyceridemia [40,52]. FGF21 deficiency in ApoE KO mice results in severe atherogenic phenotypes [53], but administering FGF21 to these ApoE KO mice ameliorates atherosclerosis [54].…”
Section: Crebh Regulates Atherosclerosis Development By Controlling Lipid Metabolism In Enterohepatic Interactionsmentioning
confidence: 99%
“…In contrast, CREBH overexpression in the liver reduces plasma triglyceride levels. CREBH overexpression in LDLR KO mice increases apolipoprotein-related genes, such as Apoa1 , Apoa4 , Apoa5 , and Apoc2 , which stimulates LPL-mediated triglyceride clearance ( Figure 2 and Figure 3 ) [ 40 , 52 ]. Conversely, deficiency of CREBH in LDLR KO mice reduces the expression of these genes, thereby inducing hypertriglyceridemia [ 40 , 52 ].…”
Section: Crebh Regulates Atherosclerosis Development By Controlling Lipid Metabolism In Enterohepatic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation